LITERATURE REVIEW : DEVELOPMENT OF AUDIO VISUAL MEDIA TO IMPROVE LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Muhammad Fa'iz Annur; Muhammad Harlanu; Bambang Subali; Ellianawati Ellianawati (PIONIR: JURNAL PENDIDIKAN, 2025)
This study is a literature review that aims to review various scientific articles on the development of audio-visual media in improving elementary school students' learning outcomes in the period 2020 to 2025. The main focus of the study is what models are used and how the results are in improving student learning outcomes. This article is a literature review that uses content analysis techniques with a Systematic Literature Review (SLR) approach based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Data collection was carried out by searching for articles in relevant national journals using the Publish or Perish (PoP) application with the Google Scholar database. The initial identification process resulted in 500 articles. Next, a screening stage was carried out based on the inclusion criteria, namely: (1) articles in accordance with the focus and keywords of the research, (2) articles published in accredited national journals, (3) articles in the form of empirical research results, and (4) articles published within the specified year range. The exclusion criteria include: (1) articles that are not relevant to the research topic, (2) duplicate articles, (3) articles in the form of opinions or non-scientific reviews, and (4) articles that are not fully accessible. Through this selection stage, 6 articles were obtained that met the criteria for further analysis in the content analysis stage. The results of the literature review of most studies using the ADDIE and Borg and Gall development models show that the use of audio- visual media can significantly improve student learning outcomes. This finding confirms that the integration of audio-visual media in learning in elementary schools has great potential to improve the quality of education. Therefore, support is needed from teachers, schools, and policy makers to continue to develop and utilize technology-based learning media optimally. Keywords: Audio Visual Media, Learning Outcomes, Elementary School, Development, Article Review